mcr-1 Identified in Fecal Escherichia coli and Avian Pathogenic E. coli (APEC) From Brazil - Nicolle Lima Barbieri; Ramon Loureiro Pimenta; Dayanne Araujo de Melo; Lisa K. Nolan; Miliane Moreira Soares de Souza; Catherine M. Logue (Frontiers in Microbiology, 2021)
Colisitin-associated resistance in bacteria of food producing animals has gained significant attention with the mcr gene being linked with resistance. Recently, newer variants of mcr have emerged with more than nine variants currently recognized. Reports of mcr associated resistance in Escherichia coli of poultry appear to be relatively limited, but its prevalence requires assessment since poultry is one of the most important and cheapest sources of the world’s protein and the emergence of resistance could limit our ability to treat disease outbreaks. Here, 107 E. coli isolates from production poultry were screened for the presence of mcr 1–9. The isolates were collected between April 2015 and June 2016 from broiler chickens and free-range layer hens in Rio de Janeiro, Brazil. All isolates were recovered from the trachea and cloaca of healthy birds and an additional two isolates were recovered from sick birds diagnosed with colibacillosis. All isolates were screened for the presence of mcr-1 to 9 using PCR and Sanger sequencing for confirmation of positive genes. Additionally, pulse field gel electrophoresis (PFGE) analysis, avian fecal E. coli (APEC) virulence associated gene screening, plasmid replicon typing and antimicrobial resistance phenotype and resistance gene screening, were also carried out to further characterize these isolates. The mcr-1 gene was detected in 62 (57.9%) isolates (61 healthy and 1 APEC) and the mcr-5 gene was detected in 3 (2.8%) isolates; mcr-2, mcr-3, mcr-4, mcr-6, mcr-7, mcr-8, and mcr-9 were not detected in any isolate. In addition, mcr 1 and 5 positive isolates were phenotypically resistant to colistin using the agar dilution assay (> 8ug/ml). PFGE analysis found that most of the isolates screened had unique fingerprints suggesting that the emergence of colistin resistance was not the result of clonal dissemination. Plasmid replicon types IncI2, FIB, and B/O were found in 38, 36, and 34% of the mcr positive isolates and were the most prevalent replicon types detected; tetA and tetB (32 and 26%, respectively) were the most prevalent antimicrobial resistance genes detected and iutA, was the most prevalent APEC virulence associated gene, detected in 50% of the isolates. Approximately 32% of the isolates examined could be classified as APEC-like, based on the presence of 3 or more genes of APEC virulence associated path panel (iroN, ompT, hlyF, iss, iutA). This study has identified a high prevalence of mcr-1 in poultry isolates in Brazil, suggesting that animal husbandry practices could result in a potential source of resistance to the human food chain in countries where application of colistin in animal health is practiced. Emergence of the mcr gene and associated colisitin resistance in production poultry warrants continued monitoring from the animal health and human health perspective.